Western Hadith Literacy In The 21st Century: A Survey of Periodical Journals Published in Europe and North America 2010-2023 - Rodliyana, M. Dede (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
This article surveys the landscape of Western hadith scholarship in the 21st century by analyzing articles published in leading scholarly journals in Europe and North America from 2010 to 2023. Employing a bibliographic survey method, this study accesses and examines articles from prominent journals such as Der Islam, Arabica, Islamic Law, and Society. The approaches used in these articles include historical analysis and isnadmatn criticism. The findings reveal that contemporary Western hadith studies have progressed beyond debates about authenticity, and now encompass more nuanced thematic and contextual analyses. The diversity of approaches to assessing the authenticity and relevance of hadith reflects the maturation of hadith studies in Western academia. The current Western scholarship on hadith demonstrates a more integrative and comprehensive approach that can serve as a valuable reference for Indonesian hadith researchers seeking to develop richer and more in-depth studies. This survey highlights the evolution of Western hadith scholarship and its potential to inspire further research in the field